2019
DOI: 10.31798/ses.641051
|View full text |Cite
|
Sign up to set email alerts
|

Ortaöğreti̇mde Görev Yapan Öğretmenleri̇n Sinif Yöneti̇mi̇ Kaygi Düzeyleri̇ni̇n İncelenmesi̇

Abstract: Öğretmenlerin sınıf yönetimi açısından temel görevi, olumlu bir öğrenme ortamı oluşturma ve öğretimin etkili olmasını sağlamaktır. Ancak günlük hayatta karşılaşılan güç ilişkileri çoğu zaman sınıf ortamında da kendini gösterebilmekte, bu durum gerek deneyimli gerekse mesleğinin ilk yıllarında olan öğretmenlerin sınıf yönetimi konusunda kaygılanmasına neden olabilmektedir. Bu araştırmanın amacı ortaöğretim kurumlarında çalışan öğretmenlerin sınıf yönetiminde yaşadıkları kaygı düzeyini belirleyerek, bazı değişke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…According to the results, an increase in sample size resulted in a decrease in anxiety level. Sadık and Nasırcı (2019) posited that teachers and students may have higher anxiety level in less crowded classrooms since in those classrooms, teachers" and students" every movement are followed up by the others easily. This may cause teachers and students not to act in a natural way, and as a result, to increase their anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, an increase in sample size resulted in a decrease in anxiety level. Sadık and Nasırcı (2019) posited that teachers and students may have higher anxiety level in less crowded classrooms since in those classrooms, teachers" and students" every movement are followed up by the others easily. This may cause teachers and students not to act in a natural way, and as a result, to increase their anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the classroom management anxiety levels of the teachers participating in the study did not differ according to the type of school and the educational status of the teachers. Sadık and Nasırcı (2019) found that high school teachers' classroom management anxiety levels were generally low. Ozgan et al (2010) and Bayrakçı and Sarı (2018) found in their studies that teachers' classroom management skills did not differ according to their educational status.…”
Section: Discussionmentioning
confidence: 96%
“…Gezen (2021) concluded that there was no significant difference between male teachers' classroom management anxiety levels and female teachers' classroom management anxiety levels. Sadık and Nasırcı (2019) state that female teachers have lower classroom management concerns than males. In this study, it is considered that classroom management concerns are high since most of the female teachers in the study group work at the high school level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for teachers who are at the beginning of their careers, their adaptation to their careers and their anxiety about being vulnerable in the classroom are among the main reasons for leaving (Mclean et al, 2019). Sadik and Nasirci (2019) reported that teachers who are at the beginning of their careers devote considerable energy to classroom management and this situation causes anxiety. Anxiety about classroom management causes poor performance in turn (Mishra & Yadav, 2013) and lowers the level of interest in the profession (Ingersoll & Smith, 2003;Özkul & Dönmez, 2021).…”
Section: Introductionmentioning
confidence: 99%